(3TQM CSeGA Gddg GdMSfis - (3eMeO Hf CHj HcQ Hf YHO GdbGOQ GdQGRj GdMfaj, Rjf GdOjf,J (B666 (3g` s ((3YHO GdhgGH Hf MSjH Gddg GdjYbhHi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf hHYO agPG eG ENJGQg GdTjN GdYdGeI eMeO GdQGRi ef cJGH GdJNjjQ ddTjN CHj GdbGSe Hf ghGRf YHO GdcQje GdbTjQi s
(3BNQgG (B:s
(3hGdUHQ GdhGLH Ydi GdYHO gh GdUHQ Ydi eG CeQg Gddg JYGdi Hg ef GdWGYGJ , hGdUHQ YeG fgi Yfg ef GdeMGQe , hGdSchf JMJ eG jLQi ef bVGFg hbOQg ced TQM s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3MhGa GdChQGb eJBcdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B55 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B112s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds